Anticancer Analysis of CD44 Targeted Cyclosporine Loaded Thiolated Chitosan Nanoformulations for Sustained Release in Triple-Negative Breast Cancer - Abduh MS (International Journal of Nanomedicine, 2023)
Maisa Siddiq Abduh1,2 1Immune Responses in Different Diseases Research Group, Department of Medical Laboratory Sciences, Faculty of Applied Medical Sciences, King Abdulaziz University, Jeddah, Saudi Arabia; 2Center of Excellence in Genomic Medicine Research, King Abdulaziz University, Jeddah, Saudi ArabiaCorrespondence: Maisa Siddiq Abduh, King Abdulaziz University, Jeddah, Saudi Arabia, Tel +00966568026868, Email mabdoh@kau.edu.saIntroduction: Cyclosporine (CsA), a potent immunosuppressive chemotherapeutic medication, treats numerous cancers, particularly malignant carcinoma, acute leukemia, and triple-negative breast cancer (TNBC).Methodology: A specified polymeric nanoformulation (NF) based drug delivery technique with ligand functionalization at the surface was developed to improve its delivery at the intended area and boost the efficacy for prolonged time. The in silico verified the HA binding to the CD44 receptor at binding sites A and B in triple-negative breast cancer cells. The NF of encapsulated Cyclosporine in thiolated chitosan (TC) with the outermost coating of hyaluronic acid (HA) was formulated and characterized.Results: So, the zeta analysis revealed a particle size of 192 nm and PDI of 0.433, zeta potential of 38.9mV. FTIR and Raman investigations also support the existence of hydrophobic groups, porous surfaces, and non-clumping characteristics. While XRD verified its crystallographic nature while SEM and TEM analysis revealed the spherical nanoparticles with sleek exteriors. DSC demonstrated the stability of NF at high temperatures. The NF showed 85% drug encapsulation followed Higuchi release model for therapeutic moiety at acidic pH for a maximum of 72 hours. When compared to raw Cyclosporine, the in vitro tumor cell inhibition of ThC-HA encapsulated with Cyclosporine was tested using an MTT dye on normal breast epithelial cells compared to triple-negative breast cancer cells.Conclusion: This novel formulation improved the long-term viability, effectiveness, and active targeting as an effective and potent therapeutic moiety against cancer.Keywords: breast cancer, CD44, cyclosporine, hyaluronic acid, nanoformulations, triple-negative breast cancer, thiolated chitosan, targeted chemotherapeutic drug delivery